Chronic toxicity studies of gandhaka rasayana - A herbo-mineral preparation used in Ayurvedic practice - Ravi Mundugaru (Elsevier, 2021)
Background: Gandhaka rasayana (GR) is an important component of many Ayurvedic formulations besides being used as a standalone therapy. However, literature review revealed a chronic toxicity studies with longer duration. Objectives: To delineate the safety profile of GR for 180 days administration in rats. Materials and methods: Wistar albino rats of both sexes weighing 150 ± 10 g body weight in groups of 20 (10 male and 10 female) for each of the three GR dose levels i.e., 0.54 g, 1.08 g, and 5.4 g/kg were employed. Carboxyl methyl cellulose was administered to the control group in equal volume. Toxicity was assessed based on the changes observed, compared to control, in body weight gain, food and water consumption, organ weight and histopathology, clinical biochemistry, and hematological parameters as per AYUSH guidelines. Results: GR repeated dose administration caused significant changes in body weight gain, organ ponderal changes, few hematologic and biochemical parameters. Male rats administered with GR at 1.08 g/kg dose showed a significant decrease in the MCV and MCH compared to control, whereas female rat’s administred with 1.08 g/kg and 0.54 g/kg dose showed a significant increase in the MCV and MCH. GR administered at 0.54 g/kg showed a significant increase in the serum glucose level in male rats, whereas female rats showed a significant elevation in the cholesterol level. GR at 0.54 g/kg and 5.4 g/kg showed a significant elevation in the serum SGPT level in male rats. These changes were not observed in female rats. Histological examination revealed mild pathological changes in organs like kidney, liver, spleen and jejunum. Conclusion: The data generated shows that GR is safe and does not have any toxicity potential at the doses used in therapeutics. Some of the changes observed were at higher dose levels which is not likely to be used clinically.